2019
DOI: 10.1210/js.2019-00119
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Supplementation and Cognitive Functioning in Men—A Systematic Review and Meta-Analysis

Abstract: Testosterone supplementation (TS) is assumed important for cognitive functioning in men, but conflicting results have prevented firm conclusions. The current study systematically reviewed available randomized controlled trials (RCTs) on effects of TS on cognitive functioning in men, subjected the findings to meta-analysis, and explored between-study differences as possible moderators of the effects. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, two authors indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
(78 reference statements)
0
14
0
1
Order By: Relevance
“…To illustrate, T administration improved cognition [ 142 ], and visual-spatial skills [ 143 ] in some cases, whereas other studies showed no positive effects on memory or mental impairment [ 144-147 ]. In a recent meta-analysis, Buskbjerg et al [ 147 ] showed that T therapy in men with normal plasma T levels had no significant clinical effect on cognitive function; T effects on men with hypogonadism remain to be evaluated.…”
Section: Androgens and Neurodegenerative Diseasesmentioning
confidence: 99%
“…To illustrate, T administration improved cognition [ 142 ], and visual-spatial skills [ 143 ] in some cases, whereas other studies showed no positive effects on memory or mental impairment [ 144-147 ]. In a recent meta-analysis, Buskbjerg et al [ 147 ] showed that T therapy in men with normal plasma T levels had no significant clinical effect on cognitive function; T effects on men with hypogonadism remain to be evaluated.…”
Section: Androgens and Neurodegenerative Diseasesmentioning
confidence: 99%
“…It is speculated that testosterone correlates with cognitive performance because hormone receptors are located near areas related to cognitive function, including the hippocampus, [18][19][20] and this hormone supports mechanisms related to cognitive function, such as increasing cerebral blood perfusion, influencing neuronal activity, and other neural-protective effects. [21][22][23][24] Similar positive associations between testosterone and cognitive ability have been described in chimpanzees, which may suggest that neuro-hormones, such as testosterone, play an important role in cognitive function 25,26 in apes and humans, as well as in other non-human primates. 27 Our findings support that old individuals with lower than normal testosterone serum level, have poorer cognitive performance.…”
Section: Analysis Of Testosterone Correlation With Cognitive Performancementioning
confidence: 54%
“…Considering these heterogenous study designs and protocols, these positive results on cognition could be the consequences of several biases. In a recently published metanalysis, Buskbjerg et al extensively evaluated the effect of T supplementation on cognition, finding a great variability in the results [ 89 ]. Particularly, different sources of bias have been verified.…”
Section: Discussionmentioning
confidence: 99%